Visibility of Spanish journals of Cinema and Audiovisual Communication in databases - Moreno-García, Mª del Carmen; Martín Moreno, Alba (Revista General de Información y Documentación, 2019)
The objective of the article is to analyse the visibility of the Spanish scientific journals on movies and audiovisual communication in the following databases: WoS, Scopus, Latindex, Cindoc-CSIC digital, and Dialnet. The methodology has been based on the calculation of the corresponding visibility indices of the 31 journals analysed. The main results are that the journals are edited by Universities in printed version as well as in double version (printed and electronic). The most frequent periodicity is the biannual, followed by the annual. The preferred language is Spanish. The calculated visibility indexes are higher in the case of national or Hispanic databases, while in international databases they are null, as in Scopus, or very low, as in the case of WoS. The need of increase the visibility of the journals analyzed in the different existing databases, especially in the international ones, is highlighted, with some proposals and suggestions for improvement.